2012
DOI: 10.3141/2281-02
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Effectiveness of Speed Feedback Signs

Abstract: Speed feedback signs (SFS), also known as dynamic speed displays, provide drivers with feedback about their speed in relationship to the posted speed limit. When appropriately complemented with police enforcement, SFS can be an effective method for reducing speeds at a desired location. However, as reported in the literature, effectiveness of SFS is limited not only in regard to time after the deployment but also for distance. Therefore, a need exists to understand how far upstream and downstream of the SFS sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The City of Boston installed speed feedback signs together with posted speed limit signs at selected locations, which previous research found to be an effective method for reducing speeds at desired locations 17 18. However, the study did not evaluate the effects of the speed feedback signs, due to a lack of sites near these signs.…”
Section: Discussionmentioning
confidence: 99%
“…The City of Boston installed speed feedback signs together with posted speed limit signs at selected locations, which previous research found to be an effective method for reducing speeds at desired locations 17 18. However, the study did not evaluate the effects of the speed feedback signs, due to a lack of sites near these signs.…”
Section: Discussionmentioning
confidence: 99%
“…Santiago-Chaparra et al [40] studied the effectiveness of a dynamic speed feedback sign on a rural two lane highway in Wisconsin. The DSFS displayed a flashing speed reading when an approaching vehicle was above the speed limit and provided a steady display when the approaching vehicles speed was below the speed limit.…”
Section: Effectiveness Of Dynamic Speed Feedback Sign Systemsmentioning
confidence: 99%
“…The effectiveness of DSFS also depends on their positioning and message. On straight sections of roadway, the greatest speed reductions are observed upstream of the sign (20,21), with diminished effects downstream of the sign (21). These findings have led to the recommendation of that the sign be positioned at or before the critical location or hazard (22).…”
Section: Introductionmentioning
confidence: 99%